Miopatia do multicore: Análise histoquímica de uma família - Resende, Luiz Antonio de Lima [UNESP]; Kimaid, Paulo André Teixeira [UNESP]; De Lima Castro, Heloísa Amélia; Fonseca, Ronaldo Guimarães [UNESP]; Dal Pai, Vitalino [UNESP]; Ueda, Anete Kinumi [UNESP]; Montenegro, Mario Rubens Guimarães [UNESP] (My University, 1998)
In this paper the authors describe three cases of multicore myopathy in the same family. Case J was a white 77-year-old patient with proximal muscular atrophy and weakness, global hypotonia and global hypoactive deep tendon reflexes. Motor and sensory conduction studies were normal in all limbs. EMG examination showed a myopathic pattern with frequent spontaneous activity consisting of fibrillations and positive sharp waves. Histochemical reactions showed typical oxidative alterations of multicore myopathy. Cases 2 and 3 were the son and the daughter of case 1 respectively. They were both non-symptomatic patients with minimal EMG and histochemical alterations. These three patients illustrated the great clinical variability of this condition.
Multicore disease: Histochemical analysis of a family
Keywords: Minicore disease; Multicore disease; Myopathy